Burden of Comorbidities and Healthcare Resource Utilization Among Medicaid-Enrolled Extremely Premature Infants - Meredith E. Mowitz; Wei Gao; Heather Sipsma; Pete Zuckerman; Hallee Wong; Rajeev Ayyagari; Sujata P. Sarda (Journal of Health Economics and Outcomes Research)
**Background:** The effect of gestational age (GA) on comorbidity prevalence, healthcare resource utilization (HCRU), and all-cause costs is significant for extremely premature (EP) infants in the United States.